APPLICATION OF MODERN INFORMATION TECHNOLOGIES IN TEACHING OF DISCIPLINES FOR STUDENTS OF EXTRA-MURAL FORM OF STUDY - Зікратий, Сергій Вікторович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The prospects of the use of internet technologies of Web 2.0 organization of educational process are considered. The chart of the informative system of support of educational process is given with the use of functions of social networks.